Fugitives, Smugglers, and Thieves : Piracy and Personhood in American Literature - Balachandran Orihuela, Sharada (Book collections on Project MUSE., 2018)
"In this book, Sharada Balachandran Orihuela examines property ownership and its connections to citizenship, race and slavery, and piracy as seen through the lens of eighteenth- and nineteenth-century American literature. Balachandran Orihuela defines piracy expansively, from the familiar concept of nautical pirates and robbery in international waters to post-revolutionary counterfeiting, transnational slave escape, and the illegal trade of cotton across the Americas during the Civil War. Weaving together close readings of American, Chicano, and African American literature with political theory, the author shows that piracy, when represented through literature, has imagined more inclusive and democratic communities than were then possible in reality"--